1994
DOI: 10.1021/ie00036a009
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Volatile Organic Compounds from Polluted Air in a Reverse Flow Reactor: An Experimental Study

Abstract: An experimental study of the reverse flow reactor for the purification of contaminated air has been carried out. An experimental reactor with a n inner diameter of 0.145 m has been constructed. It almost completely reached the goal of a n adiabatically operating system. The influence of several operating parameters such as gas velocity, cycle period, chemical character, and concentration of the pollutants and reactor pressure are discussed. The reactor could be operated autothermally provided that the inlet co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 4 publications
4
24
0
1
Order By: Relevance
“…The heat released by the reaction increases as the methane concentration in the feed increases, resulting in an increase of the width of the high temperature plateau and the value of the maximum temperature. This fact leads to higher reactor stability as reported previously in other works, 33 when working with particulate fixed-bed reactors. Moreover, if these results are compared with those reported in the literature at the same reaction conditions, but working with particulate RFR, 20 it is observed that the sensibility of the monolithic reactor to variations in inlet concentration is higher than the corresponding to particulate RFR.…”
Section: Influence Of the Main Operating Conditionssupporting
confidence: 78%
See 1 more Smart Citation
“…The heat released by the reaction increases as the methane concentration in the feed increases, resulting in an increase of the width of the high temperature plateau and the value of the maximum temperature. This fact leads to higher reactor stability as reported previously in other works, 33 when working with particulate fixed-bed reactors. Moreover, if these results are compared with those reported in the literature at the same reaction conditions, but working with particulate RFR, 20 it is observed that the sensibility of the monolithic reactor to variations in inlet concentration is higher than the corresponding to particulate RFR.…”
Section: Influence Of the Main Operating Conditionssupporting
confidence: 78%
“…This effect causes a decrease of the amount of heat trapped inside the reactor between cycles, reducing the reactor stability, as observed by the narrower temperature plateau. 33 This is more important for monolithic RFR than for particulate RFR, because the lower bed porosity reduces the thermal inertia of the bed, being more prone the reactor to extinction. The feed concentration is an important operating variable, usually subjected to constant variations when treating typical industrial gaseous emissions.…”
Section: Influence Of the Main Operating Conditionsmentioning
confidence: 99%
“…equivalent heat release in both cases), hexane presents the higher maximum temperature in all the situations tested. This is explained by the self-controlling behaviour of RFR, 18 for which slower reaction rates (hexane) produce higher operating temperatures in the central part of the bed.…”
Section: Model Validationmentioning
confidence: 99%
“…Aubé and Sapoundjiev, 8 Chaouki et al, 9 Fissore et al, 10 and Hevia et al, 11 -13 among others, also performed detailed experimental studies of methane combustion in RFRs Gosiewski et al, 14 Kushwaha et al, concentration, solid properties and switching time) on reactor performance. The catalytic combustion of other short-chain hydrocarbons, such as ethane, ethylene, propane or propene, have been studied experimentally in RFR by d Beld et al, 18,19 Ben-Tullilah et al, 20 Cunill et al, 21 Nieken et al, 22 Sheintuch and Nekhamkina, 2 and Züfle and Turek. 23 However, published works dealing with the application of RFR to the combustion of long-chain hydrocarbons are much scarcer: Matros et al 24 studied the combustion of butane and propane, and Ramdani et al 25 considered the combustion of xylene.…”
Section: Introductionmentioning
confidence: 99%
“…Except for the flow geometry, this model is similar to the extensively-studied models of the flow rever-Ž sal reactors Eigenberger and Nieken, 1988;Gawdzik and Rakowski, 1988;Thullie and Burghardt, 1990;Bhatia, 1991; . Van de Beld and Westerterp, 1994;Rehacek et al, 1998 . In our previous study of the flow-reversal operation, we did not find significant differences between the heterogeneous and homogeneous models, and we limit our simulations to the homogeneous model.…”
Section: Simulationsmentioning
confidence: 99%